The all-together quilt - Rockwell, Lizzy (Alfred A. Knopf, 2020)
In this creative story, Jennifer and her friends at the community center are making a quilt. They begin with lots of colorful fabrics and an idea. Then they measure, cut, stitch, layer, and quilt. It's the work of many hands, many hours, and many stories. And the result is something warm and wonderful they can all share. Lizzy Rockwell tells the heartwarming story of a diverse group of people coming together to make things both lasting and beautiful-- a quilt and friendship.